Disentangling HIV and AIDS stigma in Ethiopa, Tanzania and Zambia - Nyblade, Laura...[et al] (International Centre for Research on Women WashingtonUS, 2003)
Unravels some of the complexities around stigma by investigating the causes, manifestations and consequences of HIV and AIDS-related stigma and subsequent discriminatory acts in the context of Sub-Saharan Africa. Suggests programme interventions.